2006
DOI: 10.1002/pbc.20993
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial involvement at diagnosis in pediatric Hodgkin lymphoma patients

Abstract: Pericardial involvement by lymphoma is usually asymptomatic unless accompanied by substantial pericardial effusion. In most cases, pericardial involvement resolves with treatment of the underlying malignancy, but close observation for hemodynamic complications is required. A symptomatic effusion, once treated, does not affect survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…[ 9 ] In a study conducted by Bashir et al, it was seen that all patients with pericardial involvement have nodular sclerosing type of disease. [ 5 ] In other case reports also, we have found that patients had nodular sclerosing variety of HL. [ 3 4 10 ] Whether nodular sclerosing type of histology has a relationship with development of pericardial effusion needs more evaluation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…[ 9 ] In a study conducted by Bashir et al, it was seen that all patients with pericardial involvement have nodular sclerosing type of disease. [ 5 ] In other case reports also, we have found that patients had nodular sclerosing variety of HL. [ 3 4 10 ] Whether nodular sclerosing type of histology has a relationship with development of pericardial effusion needs more evaluation.…”
Section: Discussionmentioning
confidence: 72%
“…In a retrospective study consisting of 273 patients, Bashir et al, recorded only two patients with symptoms of pericardial effusion. [ 5 ] Malignant lymphoma can originate in or spread to the mediastinum. Mediastinal lymphadenopathy due to lymphoma may present early due to rapid growth of the tumor and compression caused by it.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant pericarditis can be a presenting manifestation in exceptional cases [12]. Nevertheless, in pediatric HL, 5% of patients, exclusively with nodular sclerosis subtype, had evidence of pericardial infiltration, although only two of 13 required fluid drainage and none demonstrated malignant cytology [13]. Invasion of pericardium has been described in HL almost exclusively with bulky disease exceeding one third of the thoracic diameter [14].…”
Section: Discussionmentioning
confidence: 99%
“…Bashir et al . explained the pathogenesis of cardiac involvement in lymphoma in their 2006 study [ 10 ]. One sixth of neoplastic pericardial diseases are caused by hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with suspected bone involvement usually undergo bone scans, while patients in the advanced stages of the disease undergo bone marrow biopsies. Baseline studies consist of a complete blood count, blood chemistry analyses, kidney and liver function tests, echocardiography, electrocardiography, and pulmonary function tests [ 10 ].…”
Section: Introductionmentioning
confidence: 99%